2001
DOI: 10.1037/0278-7393.27.5.1314
|View full text |Cite
|
Sign up to set email alerts
|

A limit on retrieval-induced forgetting.

Abstract: Retrieving some members of a memory set impairs later recall of semantically related but not unrelated members (M. C. Anderson, R. A. Bjork, & E. L. Bjork, 1994; M. C. Anderson & B. A. Spellman, 1995). The authors investigated whether this retrieval-induced forgetting effect would generalize to testing procedures other than category-cued recall. Although the authors demonstrated a retrieval-induced forgetting effect using a category-cued recall task, they failed to show retrieval-induced forgetting on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
81
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 14 publications
(48 reference statements)
10
81
7
Order By: Relevance
“…Anderson et al (1994) found retrievalinduced forgetting, both when providing category cues at test and when providing additional item-specific cues, such as the first two letters of the target items. Butler, Williams, Zacks, and Maki (2001) replicated the result with respect to category cues but failed to show retrieval-induced forgetting on tests using item-specific cues, such as categoryplus-stem-cued recall or category-plus-fragment-cued recall. We used category-plus-first-letter cues to control the subjects' output sequence and found reliable retrievalinduced forgetting and reliable part-list cuing.…”
Section: The Role Of Item-specific Cues In Retrievalinduced Forgettinsupporting
confidence: 56%
“…Anderson et al (1994) found retrievalinduced forgetting, both when providing category cues at test and when providing additional item-specific cues, such as the first two letters of the target items. Butler, Williams, Zacks, and Maki (2001) replicated the result with respect to category cues but failed to show retrieval-induced forgetting on tests using item-specific cues, such as categoryplus-stem-cued recall or category-plus-fragment-cued recall. We used category-plus-first-letter cues to control the subjects' output sequence and found reliable retrievalinduced forgetting and reliable part-list cuing.…”
Section: The Role Of Item-specific Cues In Retrievalinduced Forgettinsupporting
confidence: 56%
“…However, this explanation is unlikely because several of the boundary conditions under which retrieval-induced forgetting effects disappear are present in our study: relational processing of the material during learning (e.g., Anderson & McCulloch, 1999), the use of specific retrieval cues on the criterial test (i.e. as opposed to category cues; e.g., Butler, Williams, Zacks, & Maki, 2001), and retention intervals longer than 24 hours (e.g., MacLeod & Macrae, 2001). …”
Section: Resultsmentioning
confidence: 78%
“…The possibility of explicit contamination is always a concern in research using implicit memory tests (e.g., Mulligan, 2002;Mulligan & Hartman, 1996). The fact that participants in the Butler et al (2001) study detected the relation between the test phase and the study and practice phases indicates that this is indeed possible. Noticing this connection could have triggered explicit retrieval of the category, RPϩ items, and NRP items, which could have influenced the response latencies for the RPϪ items in Veling and van Knippenberg's experiment.…”
mentioning
confidence: 99%
“…Unlike what is done in explicit memory tasks such as category-cued recall, no reference is made to the study phase in implicit memory tasks. Butler, Williams, Zacks, and Maki (2001) used a wordfragment completion task to test implicit memory in the retrieval-practice paradigm. They did not obtain retrievalinduced forgetting.…”
mentioning
confidence: 99%
See 1 more Smart Citation